ADAPTIVE HOMESTAY SEBAGAI BENTUK PARTISIPASI MASYARAKAT UNTUK MELESTARIKAN DESA WISATA PENTINGSARI - YOGYAKARTA - Vincentia Reni Vitasurya (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2016)
Title: Adaptive Homestay as a Form of Community Participation to Preserve Pentingsari Tourist Village, Yogyakarta The development of tourism in a tourist destination is linked to the development of economic sectors in the region or the country. The development of tourism is expected to bring benefits to the community. Yogyakarta as one of the tourist destinations has developed a range of alternatives that can be offered to travelers. Pentingsari tourist village is one of the mainstay tourism village in Yogyakarta. The village has been proven to run well and maintained its continuity since 2008. Preservation of the village was made possible through the participation of citizens to participate and engage in their village tourism activities. One that supports the success of ecotourism activities is homestay. In relation to the tourism industry, homestay can be described as two things: as a tourist attraction and as a tourist accommodation. Pentingsari village already has homestays which are village houses that already run well. This research seeks homestay relevance as a form of citizen participation in the rural tourism industry while maintaining the conservation of the environment. The methods used is participatory research action by field observation, in depth interviews and historical documents tracing. This is to determine how much the role of citizens to preserve the environment before and after becoming a tourist village. These results indicate a model of rural tourism development.